Perlindungan Kreditor atas Gagal Bayar Kredit Tanpa Agunan dalam Koperasi Syariah - Saputro, Neno Achmad Wahyu; Winarno, Bambang; Purborini, Vivi Sylvia (RechtJiva, 2026)
Unsecured credit schemes are widely implemented by sharia-based cooperatives to support members’ financial needs. However, the absence of collateral increases the risk of default and weakens the legal position of creditors. This study aims to analyze the forms of legal protection available to creditors and the mechanisms for resolving default in unsecured credit agreements within a sharia cooperative environment. The research employs an empirical legal method with a sociological-juridical approach. Data were collected through interviews with cooperative management and analysis of relevant documents, including internal policies and credit agreements. The findings reveal that creditor protection is primarily implemented through prudential principles, particularly the application of the 5C analysis (Character, Capacity, Capital, Collateral, and Condition), although the collateral element is not physically applied. Legal protection is further strengthened through written agreements, salary-deduction mechanisms, internal mediation, and persuasive settlement approaches. When non-litigation efforts fail, legal action remains an available option based on general civil law provisions. This study concludes that despite the absence of collateral, creditors can obtain adequate legal protection through preventive and repressive legal measures, provided that contractual clauses are formulated clearly and prudential principles are consistently enforced. Strengthening contractual arrangements is essential to ensuring legal certainty and minimizing financial risks for sharia cooperatives.